Aprimoramento das propriedades térmicas e mecânicas de isolantes refratários macroporosos - Finhana, Icaro Caldeira (Universidade Federal de São Carlos, 2024)
The pursuit of environmentally friendly and health-conscious solutions has driven the replacement of ceramic fiber-based thermal insulators with macroporous refractories. The latter offer several benefits, including reduced thermal conductivity at high temperatures and toxicity, depending on the processing route applied. The literature underscores that surfactant-stabilized foams, achieved through the direct foaming of an optimized blend of raw materials and additives, yield highly porous ceramics with appropriate mechanical strength and thermal conductivity. Furthermore, the introduction of CaCO3 into alumina-based compositions has emerged as an effective means to lower the mechanical strengthening temperature (TS) and counteract the sintering-induced shrinkage of these porous refractories through in situ formation of CA6. However, such systems have not yet attained the desired pore size and require pre-firing at elevated temperatures before installation. Aiming to enhance these materials, diverse approaches have been examined. Firstly, the reduction of the particle size of calcium aluminate cement (CAC), utilized as a binder, was investigated for both ultrastable systems and those stabilized by surfactants. This led to a decrease in the average pore size in the former case but yielded no significant alterations in the latter. Hence, for the latter case, pre-expanded polymeric microspheres (Expancel) were utilized as a sacrificial template to generate smaller pores. The combination of direct foaming with the incorporation of these microspheres resulted in highly porous ceramics with suitable mechanical strength and lower thermal conductivity (0.36 - 0.49 W.m-1.K-1). Finally, with the aim of reducing energy consumption during the sintering of these ceramics, the use of microwaves was assessed. It was concluded that a firing process at 1400 °C for 15 minutes, proved sufficient to sinter these materials and produce an amount of CA6 equivalent to traditional firing at 1600 °C for 5 hours, delivering substantial time and energy savings.
Enhancing the thermal and mechanical properties of macroporous refractory insulators
Keywords: Refratários macroporosos; Espumação direta; CAC; Expancel; Micro-ondas; Macroporous refractories; Direct foaming; CAC; Expancel; Microwaves; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA